Trends and Characteristics of Young Non-Small Cell Lung Cancer Patients in the United States - Thomas, Anish; Chen, Yuanbin; Yu, Tinghui; Jakopovic, Marko; Giaccone, Giuseppe (Frontiers in Oncology, 2015)
Background: Although the median age at diagnosis of NSCLC is 70 years, a subset of patients with NSCLC present at a younger age (<40 years). Little is known about the time-trends in incidence of NSCLC in the young, their characteristics and outcomes. Methods: The Surveillance, Epidemiology, and End Results (SEER) database was used to extract NSCLC cases from 1978 to 2010. Yearly incidence rates in various age groups, race, site of disease, histology, treatment patterns and outcomes were assessed. We modeled Kaplan-Meyer survival curves stratified by age of presentation. Results: Young patients represented 0.6% of incident NSCLC from 1978 to 2010. The incidence of young NSCLC declined significantly during this time-period. Young NSCLC's had a higher proportion of women (51%), Asians or Pacific Islanders (14%), adenocarcinoma histology (59%) and were more likely to present with distant metastases (68%). The young had better all cause and lung cancer-specific survival than the older patients (median survival for localized, regional and distant disease: not reached, 28 months, 9 months vs. 46 months, 17 months, 5 months; P <0.001 for all groups). Male sex, non-adenocarcinoma histology and main bronchial primary were independent negative prognostic factors among the young. In contrast to the overall population, black race was a poor prognostic factor among the young. Conclusions: The incidence of NSCLC in the young decreased from 1978 to 2010. The clinical characteristics of NSCLC in the young, including demographic distribution, treatment, and outcomes are different from those observed in the older patients.